Development of Animation Video Based Media as Health Promotion Media regarding Providing MP-ASI to Mrs. Baduta - Jayanti, Lovina; Sopingi, Sopingi; Ratih, Suci Puspita (SEAN Institute, 2024)
Early complementary feeding behavior (<6 months) is still common in Indonesia, especially in East Java. Based on the results of a preliminary study in one area of ​​East Java, namely Wonocolo District, Surabaya City, it was found that 80% of mothers gave early complementary foods. Therefore, a special program is needed to reduce the rate of early complementary feeding behavior, one of which is by providing education using media as a tool. Animated video is the media most chosen by the target. The main focus of this research is the development of animated video media which includes feasibility and effectiveness. The type of R&D research applied in this study took a one group pre-test post-test trial design. There were 4 treatments given to 30 targets in the trial stage, namely the pre-test, the provision of animated video media viewed at the same time and place, assessing the media, and also the post-test. After conducting the validation test, this animated video was considered very feasible by experts, namely material experts and media experts. This animated video is also considered effective, seen from the results of the paired sample t-test which shows a sig value. (2-tailed) 0.000 which is <0.05. This means that there is a difference in the average value of knowledge before and after being given animated video media. This shows that this animated video electronic media is very feasible and effective as a health education media on appropriate complementary feeding.